Subtle immunodeficiencies in nodular–bronchiectatic Mycobacterium avium complex lung disease - Bruno, Mariolina (ERJ Open Res, 2020)
Patients with nodular–bronchiectatic MAC lung disease have dysregulated adaptive immunity with defective IL-17 and IFN-γ production, and IL-10 overproduction. This suggests a role for adjunctive immunomodulatory treatments. https://bit.ly/33AALwx